The Use of Media in the Dissemination of Development Information in Kaitetu Village - Yuniar Sakinah Waliulu; Fatmawaty Rumra (CV. Publikasi Indonesia, 2025)
Communication is a basic human activity. By communicating, humans can relate to each other in daily life in the household, at work, in the market, in society, or wherever humans are. There is no human being who will not be involved in communication. Communication is very important for human life. The development of human knowledge from day to day is due to communication. Communication also forms a social system that needs each other. Therefore, communication and society cannot be separated. This research aims to get an overview of media literacy in terms of using and utilizing the media to convey several messages to cause understanding and changes in community behavior. The final goal of this research is to create a role model of development communication with a media literacy study as a reference. The following is an important point of the purpose of this research: to find out how effective the use and utilization of media is. This research uses descriptive qualitative methods. The type of data in this study uses qualitative data types; the main data sources in qualitative research include informants' ideas, expressions, and views on development communication and media literacy in delivering a number of messages. The informants in this study were selected using purposive sampling. The informants in this study were the government staff of Negeri Kaitetu Central Maluku. This research found that the Kaitetu State Government, in disseminating development information, makes good use of the media; this can be seen from the use of traditional media and new media, such as social media, in disseminating development information in Kaitetu State. The mandatory output that is the target of this research is that the research results will be published in the form of accredited national journals and intellectual property rights. In addition to mandatory outputs, there are also additional outputs in the form of books. This research output is published in the form of articles mentioning the journal's name and the publisher's name, and TKT is Social Humanities and Education.